Impact of Aggression and Perceived Stress on the Social Competence of Adolescent Girls with Living and Deceased Parents - Shah, Inayat; Zia, Kainat; Ali, Humaira; Sarwar, Naveeda (The Lighthouse Journal of Social Sciences, 2024)
Teenagers are an asset to every nation, and young women play a crucial part in the development of a nation’s capabilities. This study revealed that an increase in aggression and perceived stress diminishes the social competence of adolescent females and that the parents’ status (life/death) significantly affects their aggression level. This paper explored the relationship between adolescent girls’ aggression, perceived stress, and social competence by explicating the impact of aggression and perceived stress on social competence. This study also revealed differences in mean test results based on parental status (alive or dead). The sample consisted of 230 girls between the ages of 12 and 18 years old. Utilizing a correlational study design and a purposive sampling technique, participants were provided with standardized measuring instruments. The statistical analysis revealed that aggression has a significant negative effect on the social competence of adolescent girls. Furthermore, the correlation analysis of aggression and perceived stress revealed a significant negative relationship with social competence and a significant positive association between aggression and perceived stress in the sample. The mean analysis elucidated substantial differences in the aggressiveness scores of teenage girls based on parental status (alive/deceased). This article would inform clinical psychologists, education counselors, psychologists, clinicians, family members, and educators about the possible causes of aggression, perceived stress, and poor social skills in teenagers, allowing them to design better interventions to improve their skills and personality.